The methods of obtaining haploids in the cell winter wheat breeding (a review) - N. V. Kalinina; S. G. Golovko; E. V. Ionova (Зерновое хозяйство России)
The purpose of the current study was to identify the role of haploid plants in the grain crops’ breeding, to analyze the methods of obtaining haploids in vitro, and to compare the efficiency of the conventional and cell methods of winter wheat breeding. The current paper has considered the biotechnological methods of obtaining dihaploid lines, which could fasten the breeding process by 1.5–2 times and improve the quality of products. There has been established that the agricultural crops’ breeding based on intraspecific hybridization and selection is still a long and labor consuming process (10–12 years). There has been given characteristics of such methods used in vitro as androgenesis in the isolated anthers and microspores, gynogenesis, distant hybridization followed by selective elimination of chromosomes. There has been established that biotechnological methods would allow breeders to work with the necessary traits, and the highly productive and adaptable lines obtained in a year should be included in hybridization. There have been shown the main stages of the technology for obtaining haploid plants in anthers of grain crops, namely a growing and selection of donor plants, pretreatment with various stress factors, isolation of anthers and their cultivation in vitro, inducing embryogenesis, plant regeneration, doubling the number of chromosomes of regenerant plants. There have been considered some factors controlling the induction of callusogenesis, embryoidogenesis and plant regeneration in vitro of cereals. Thus, there has been established an efficiency of cell breeding of winter wheat in comparison with conventional methods of breeding.